Computer-aided Instruction and Institutional Effectiveness of Federal Polytechnic in North Central Nigeria - Ogundele, Michael Olarewaju; Udokang, Anietie E (Pakistan journal of education, 2016)
The study investigated the relationship between computer aided instruction and institutional effectiveness of Federal Polytechnics in the North Central Geo-Political Zone. Correlation design was adopted for the study. Stratified random sampling technique was used to select 1000 respondents comprising of Heads of Departments, Examination officers, library and Information Technology officers, Chief Lecturers, Students and Executives of Student Union Governments. The research instruments used for the study were Questionnaires; Computer Aided Instruction Questionnaire (CAIQ) and Institutional Effectiveness Questionnaire (IEQ). The instruments were validated by the experts of computer science and science education. Split-half reliability method was used to determine reliability index of 0.62 and 0.64 for CAIQ and IEQ respectively after subjecting to Spearman ranking order statistics at 0.05 significance level. Three research questions and four hypotheses were generated to guide the study. Descriptive statistics was used to answer the research questions while Pearson product moment was used to test all the hypotheses. The result shows that there is low significant relationship between computer aided instruction and institutional effectiveness of Federal Polytechnics in North Central Nigeria. It was however recommended that adequate computer accessories should be provided for effective teaching and learning processes in the polytechnic. Also, adequate computer and utilization training should be given to all lecturers in order to develop computer based instruction for the effectiveness of the instruction in North Central Nigeria.